Effect of Partnership Status on Preferences for Facial Self-Resemblance - Lindová, Jitka; Little, Anthony C.; Havlíček, Jan; Roberts, S. Craig; Rubešová, Anna; Flegr, Jaroslav (Frontiers in Psychology, 2016)
Self-resemblance has been found to have a context-dependent effect when expressing preferences for faces. Whereas dissimilarity preference during mate choice in animals is often explained as an evolutionary adaptation to increase heterozygosity of offspring, self-resemblance can be also favoured in humans, reflecting, e.g., preference for kinship cues. We performed two studies using transformations of facial photographs to manipulate levels of resemblance with the rater, to examine the influence of self-resemblance in single versus coupled individuals. Raters assessed facial attractiveness of other-sex and same-sex photographs according to both short-term and long-term relationship contexts. We found a preference for dissimilarity of other-sex and same-sex faces in single individuals, but no effect of self-resemblance in coupled raters. No effect of sex of participant or short-term versus long-term attractiveness rating was observed. The results support the evolutionary interpretation that dissimilarity of other-sex faces is preferred by uncoupled individuals as an adaptive mechanism to avoid inbreeding. In contrast, lower dissimilarity preference of other-sex faces in coupled individuals may reflect suppressed attention to attractiveness cues in potential alternative partners as a relationship maintenance mechanism, and its substitution by attention to cues of kinship and psychological similarity connected with greater likelihood of prosocial behavior acquisition from such persons.